Dendrobium nobile Lindl. Alkaloids Decreases the Level of Intracellular β-Amyloid by Improving Impaired Autolysosomal Proteolysis in APP/PS1 Mice - Nie, Jing; Jiang, Lin-Shan; Zhang, Yu; Tian, Yong; Li, Li-Sheng; Lu, Yan-Liu; Yang, Wen-Jin; Shi, Jing-Shan (Frontiers in Pharmacology, 2018)
As the major degradation pathway for long-lived proteins and organelles, macroautophagy is a decisive factor for the survival and longevity of cells. The existing evidence indicates that the disruption of substrate proteolysis in autolysosomes is the main mechanism underlying autophagy failure in Alzheimer’s disease (AD). Thus, the restoration of normal lysosomal proteolysis and autophagy efficiency is a novel therapeutic strategy in the treatment of AD. In this study, 9-month-old APPswe/PS1ΔE9 transgenic (APP/PS1) mice were administered Dendrobium nobile Lindl. alkaloids (DNLA, 40 and 80 mg/kg) or Metformin (80 mg/kg), and age-matched wild-type mice were administered an isovolumic vehicle orally once a day for 4 months. The results demonstrated that DNLA significantly improved learning and memory in APP/PS1 transgenic mice in the Morris water maze. Furthermore, DNLA could increase the expression of the v-ATPase A1 subunit to facilitate lysosomal acidification, prompt the dissociation of the cation independent-mannose-phosphate receptor from cathepsin (cat) D, promote the proteolytic maturation of cat D, increase the degradation of accumulated autophagic vacuoles (AVs) and β-amyloid (Aβ) contained in the AVs, and alleviate neuronal and synaptic injury. These findings demonstrate that DNLA improves learning and memory function in APP/PS1 mice, and the mechanisms appear to be due to the promotion of intracellular Aβ degradation by increasing the protein level of v-ATPase A1 and then improving autolysosomal acidification and proteolysis.